Cross sections for nu(mu) and (nu)over-bar(mu) induced pion production on hydrocarbon in the few-GeV region using MINERvA - McGivern, CL (2016)
This work was supported by the Fermi National Accelerator Laboratory under U.S. Department of Energy Contract No. DE-AC02-07CH11359 which included the MINERvA construction project. Construction support was also granted by the United States National Science Foundation under Award No. PHY-0619727 and by the University of Rochester. Support for participating scientists was provided by NSF and DOE (U.S.A.), by CAPES and CNPq (Brazil), by CoNaCyT (Mexico), by CONICYT (Chile), by CONCYTEC, DGI-PUCP and IDI/IGI-UNI (Peru), and by Latin American Center for Physics (CLAF). We thank the MINOS Collaboration for use of its near detector data. We acknowledge the dedicated work of the Fermilab staff responsible for the operation and maintenance of the beam line and detector, and we thank the Fermilab Computing Division for support of data processing.